Effect of solvent volume on properties of SnO2:Al films. (June 2013) - Thirumurugan, K; Ravichandran, K; Mohan, R; Snega, S; Jothiramalingam, S; Chandramohan, R
Abstract : Aluminium doped tin oxide films (ATO) were deposited from starting solutions having different solvent volumes (10, 20, …, 50 mL), using a simplified spray pyrolysis technique and the effect of solvent volume on the structural, optical and electrical properties was investigated. Structural studies revealed that Al 3+ incorporation into the Sn 4+ sites of the SnO2 lattice is gradually increased with increasing solvent volume. The variation in the preferential orientation factor f (110) as a function of solvent volume is discussed in detail. From electrical studies, it is found that the sheet resistance R sh is minimum (3·98 kΩ sq −1 ) when the solvent volume is minimum, and R sh increases as the volume of the solvent increases. The gradual decline in the intensity of the peak at 411 nm of the photoluminescence spectra indicated the decrease in the density of oxygen vacancies. The optical transmittance in the visible region is higher (85%) for higher solvent volume.